From ownership to access: How the sharing economy is changing the consumer behavior - Cătălin Mihail Barbu; Dorian Laurenţiu Florea; Radu Florin Ogarcă; Mihai Constantin Razvan Barbu (Amfiteatru Economic Journal, 2018)
Promoting the principles of circular economy and the new business models advocated by the circular economy can represent a solution for a more prosperous society, less dependent on primary and energy resources and more environmentally friendly. The sharing economy, which primarily involves the transformation of traditional market behaviors into collaborative consumption models, that ensure a more efficient and sustainable use of resources, is part of the circular economy and has generated business models that are compatible with it. This article discusses the possibility for the sharing economy to bring about profound changes in consumer behavior towards products and services and to highlight the factors that drive consumers' shift towards the sharing economy. For this purpose we developed and tested a model in which the change in consumer mindset has as the main direct determinants the satisfaction with the services of the sharing economy and the intention to access such products and services. The study uses data collected through a questionnaire, applied to a sample of 320 customers of Uber - a symbol of the sharing economy, and processed using structural equation modelling. Research results show that there are premises for switching to an access-based consumption model.
Keywords: O33; Q53; M30; 330; circular economy; sharing economy; collaborative economy; consumption pattern; consumer behavior